2019
DOI: 10.1177/2150135118809076
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Acute Mitral Regurgitation Due to Chordal Rupture in Infants: Surgical Management and Results

Abstract: Objective: Emergency surgical treatment is required for idiopathic acute mitral regurgitation due to chordae rupture in infants. Nevertheless, mitral valve repair for such a patient population still remains challenging. We report our experience with mitral valve repair for idiopathic acute mitral regurgitation due to chordae rupture in infants. Methods: From 2005 to 2017, six infants (four boys) were diagnosed with acute mitral regurgitation due to chordae rupture and underwent mitral valve repair. The median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Yoshizawa et al . [ 5 ] reported six infants with idiopathic acute MR who underwent edge-to-edge mitral valve repair. The authors used Kay’s annuloplasty and artificial chordae in some cases and reported no early or late deaths or reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…Yoshizawa et al . [ 5 ] reported six infants with idiopathic acute MR who underwent edge-to-edge mitral valve repair. The authors used Kay’s annuloplasty and artificial chordae in some cases and reported no early or late deaths or reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…In all patients, mitral valve repair was performed, and concomitant cardiac lesions were also repaired (Table 2). As described previously, 5 CV-5 or CV-6 sutures (W. L. Gore & Associates, Inc.) were used as artificial chordae. In patients with posterior mitral leaflet hypoplasia, especially in the P2 region, an autologous pericardium treated for 3-5 minutes with 0.625% glutaraldehyde was applied to augment the posterior leaflet.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of lesions the affected broad segments or center of leaflets, especially the anterior leaflet, artificial chordal reconstruction was attempted. 5…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Yoshizawa et al from Hyogo published in the WJPCHS the first paper that selectively reports on a group of infants with acute mitral chordal rupture. 12 There is a detailed description of the typical presentation and the use of polytetrofluoroethylene chordal implantation, edge-to-edge suture, and Kay annuloplasty. They stress the need for prompt transfer to theatre and for 48 h of sedation afterward to avoid hypertension in the early phase postoperatively.…”
Section: Doi: 101177/21501351221114774mentioning
confidence: 99%